ECONOMIC PENETRATION OF AUSTRO-HUNGARY AND RUSSIA IN THE ОTTOMAN EMPIRE IN THE LAST THIRD OF XIX - THE BEGINNING OF XX CENTURIES - Igor V. Kryuchkov (Наука. Инновации. Технологии)
The article deals with the question of peculiarities of foreign economic re-lations between Russia, Austro-Hungary and Ottoman Empires and the issue of competition of Vienna and St. Petersburg in the markets of the Middle East and the Balkans. Key words: export, Austro-Hungary, Russia, commercial treaty, foreign trade.